Strategic Quality Management in Education: The Roles of Principal and Deputy Principals - Uswatun Khasanah; Yatim Riyanto; Sri Setyowati (Indonesia Approach Education, 2022)
This study is qualitative research which is framed as a case study. It is aim for analyzing the roles of Principal and Deputy Principals in strategic quality management at school. Data were collected through semi structured interviews, passive-participant observation, and study of documents. The document analysis and inductive method were used in analyzing the data. Results show that Principal and Deputy Principals play important roles in strategic quality management. Setting out a shared vision statement is crucial to build high commitment to reach the common goals. Setting out priorities and policies While effective team coordination brings good atmosphere to synergy and unity in the pursuit of common goals. Systematically checking of effectiveness through periodical monitoring and evaluation is for ensuring the process meet the quality standard. Transmitting the results of monitoring both to staff and to Principal- Top management is to bring better improvement. Keywords: School management, quality management, strategic quality management